Late Triassic sedimentary geochemistry and tectonic significance in the Yajiang Basin, sichuan - Wang, H.; Ruan, L.; Guo, J.; Wang, Xuan-Ce; Liu, Q.; Liang, B.; Li, Z.; Wang, B. (2012)
Eighteen clastic sedimentary rock samples from the Triassic typical section in the Yajiang Basin are analyzed. The SiO 2 content changes mainly from 70% to 90% and the Al 2O 3 content is mainly from 8% to 10%, which indicates weak carbonization. The REE analysis shows that the Triassic sandstone from the Yajiang Basin is characterized by typical supracrustal enclaves. The LaN/YbN ratio indicates that the Yajiang Basin group and Zagunao group are the border of the continental island arcs and passive continent. The Eu/Euratio from the Yajiang group and Xinduqiao group is greater than that of the other two groups, which indicates their sources are different. Ce exception indicates that the redox conditions in the sedimentary environments change greatly. The analysis of Al 2O 3/SiO 2, K 2O/N 2O, and Fe 2O 3+MgO shows that the sources of the Yajiang Basin are mainly acid rocks. La-Th and Zr-Th discrimination diagrams and functions are used. The comprehensive analysis of the study leads to the conclusion that the geochemical characteristics of the Yajiang group, Lianghekou group, Xinduqiao group, and Zagunao group in the Yajiang Basin in the late Triassic period reflect the respective tectonic backgrounds: active continental margin, continental island arc, and passive continental margin.